1968
DOI: 10.2136/sssaj1968.03615995003200030019x
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Properties of a Clay Loam Soil and the Field Measurement of Water Uptake by Roots: II. The Water Balance of the Root Zone

Abstract: Soil water depletion rates in a 115‐cm and a 170‐cm deep profile of Adelanto clay loam were compared with lysimetrically obtained consumptive use rates for periods of many days after measured water applications. When the soil was bare, the depletion rates were always higher than the rate of loss to the atmosphere, and the inferred flux at the 170‐cm depth was as high as 2 mm/day 8 days after irrigation. When the test plot was planted to sorghum (Sorghum vulgare Pers.) an initially strong downward flux at the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Th is interaction could be important for increased plant available water (Van Bavel et al, 1968;Allmaras et al, 1975;Van Bavel and Ahmed, 1976;Stuff and Dale, 1978), solute transport back into the root zone (Berkowitz et al, 2004;Logsdon, 2007;Abit et al, 2008), soil water variation at diff erent landscape positions (Logsdon et al, 1999), possible evapotranspiration variation at diff erent landscape positions (Chen and Hu, 2004), and surface and lateral redistribution of soil water and eff ect on tile drainage (James and Fenton, 1993;Khan and Fenton, 1994;Kohne and Gerke, 2005). Further study is needed to quantify these eff ects in agricultural landscapes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th is interaction could be important for increased plant available water (Van Bavel et al, 1968;Allmaras et al, 1975;Van Bavel and Ahmed, 1976;Stuff and Dale, 1978), solute transport back into the root zone (Berkowitz et al, 2004;Logsdon, 2007;Abit et al, 2008), soil water variation at diff erent landscape positions (Logsdon et al, 1999), possible evapotranspiration variation at diff erent landscape positions (Chen and Hu, 2004), and surface and lateral redistribution of soil water and eff ect on tile drainage (James and Fenton, 1993;Khan and Fenton, 1994;Kohne and Gerke, 2005). Further study is needed to quantify these eff ects in agricultural landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Shallow water tables contribute to upward capillary movement into the root zone to replenish soil water lost from root uptake (Van Bavel et al, 1968;Allmaras et al, 1975;Van Bavel and Ahmed, 1976;Stuff and Dale, 1978;Chen and Hu, 2004;Loheide, 2008), unless the water table is so shallow that root activity is restricted (Nielsen et al, 1959;Williamson and Kriz, 1970;Carter et al, 1988). Th is contributes to a smaller range of soil water content over the growing season for toeslope positions (Logsdon et al, 1999), even though overall water uptake may be greater for toeslope positions than for upslope positions.…”
mentioning
confidence: 99%
“…Field measurement of field capacity was facilitated by development of the neutron probe. Burrows and Kirkham (1958) Field studies related to deep percolation Many papers have been published concerning moisture and tension changes in the field during and after water application, (Hilgeman, 1948;Cannell and Stolzy, 1962;Richards ^ al., 1956;Ogata and Richards, 1957;Wilcox, 1959;Wilcox, 1960;Nielsen et a^., 1964;and van Bavel et al, 1968a). Richards (1956) reported results from an experiment where bare soil was deeply irrigated with water containing a known concentra tion of chloride.…”
Section: Field Capacitymentioning
confidence: 99%
“…The rate of drainage out of a slab of soil was assumed to be a function of its total water content. The model was designed to predict the seepage rate with time out of the soil slab, subtract the seepage from total use rate, and calculate évapotranspiration rate, van Bavel et al (1968a) found the method accounted for rapid drainage immediately after irrigation but it failed after extended periods of drainage because the potential gradient at the base of the root zone was not considered. Nielsen et al (1964) The principal disadvantage of the field technique was that the conductivity was defined for only a narrow range of moisture contents.…”
Section: Prediction Of Deep Percolationmentioning
confidence: 99%
See 1 more Smart Citation